Naval aviation in the Second World War rare photographs from wartime archives - Kaplan, Philip (Images of War, 2013)
A new and exciting addition to the well-regarded Images of War series. Features a library of intriguing photographs that illustrate the conflict, paired with text from the author setting the images in context.